The effectiveness of nutritional information on foodservice companies' corporate social responsibility. Issue 1 (1st January 2017) - Choi, Jinkyung
Abstract: The objective of this study is to investigate the effect of nutritional information disclosure and healthful menu context in the relationship of nutritional knowledge and consumers' perceived CSR toward a foodservice company. Furthermore, the relationship among CSR, brand image, attitude and purchase intention was investigated. The study was designed with scenario experimental questionnaires: 3 (different nutritional information levels: no information, calorie only and content with six segments of nutritional information) X 2 (menu context: healthy or unhealthy menu context). Confirmatory factor analyses, structural equation modelling and analysis of variance analysis were used in order to examine the study hypotheses. The results of this study indicate that consumers' nutritional knowledge helps increase consumers' perceived CSR which has an impact on brand image, attitude and behavioural intention, however, no moderating effects of nutritional knowledge and healthful menu context were found. Furthermore, purchase intention was significantly affected by CSR, attitude and brand image. Therefore, disclosure of nutritional information and offering healthful menu would help restaurants gain a positive CSR which also would help them to expect consumers' favourable purchase intention.